PROMOTING STUDENTS’ SPEAKING ACHIEVEMENT THROUGH REPORTING TECHNIQUE - Arief Pamuji (FKIP Universitas Tridinanti, 2022)
This research aimed to promote the speaking achievement of the second STIK Bina Husada Palembang midwifery students using reporting technique. This research used a quasi-experimental method, with a non-equivalent group design for the pre-test and post-test. The population consisted of 38 students who were as sample from STIK Bina Husada Palembang's second-semester midwifery students. The sample taken by using total sampling technique to obtained the sample. In collecting the data, a speaking test was utilized. The test was found to be both valid and reliable. The value of t-obtained (5.59) was greater than t-table (2.02) at the significant level of ρ 0.05, according to the results of the independent t-test. It was concluded that the reporting technique could promote students’ speaking achievement. It meant that this technique could help students improve their speaking skills. The reporting strategy proved effective in teaching second-year midwifery students how to interpret a recount text. As a result, it can be concluded that reporting technique can be used by students to improve their speaking English, and teachers can use this technique in teaching and learning the students in order to increase and motivate the students' speaking in STIK Husada Bina.